Microstructure of a Ce0.1Zr0.9O2–MgAl2O4 Ceramic Matrix Composite for Use in Dentistry. Issue 5 (11th January 2014) - Krumeich, Frank; Wörle, Micheal; Nesper, Reinhard; Höland, Marlies; Ritzberger, Christian; Rothbrust, Frank; Chevalier, Jerome; Rheinberger, Volker M.; Höland, Wolfram; Chen, I.‐W.
<x xml:space="preserve">Abstract</x> A ceramic matrix composite (CMC) with the chemical composition of 90 wt% Ce0.1Zr0.9O2 and 10 wt% MgAl2O4 was produced by filter‐pressing, drying, and heat treatment at 1400°C. The internal microstructure was studied using the transmission electron microscopy (TEM) technique combined with energy‐dispersive X‐ray spectroscopy. Because of the intended use in dentistry, the surfaces of the as‐fired and of the mechanically treated samples were characterized by atomic force microscopy (AFM) and X‐ray diffraction (XRD Rietveld analysis). This study revealed that Ce0.1Zr0.9O2 and MgAl2O4 spinel are the only crystalline phases present in the CMC material. Nevertheless, apart from the tetragonal Ce0.1Zr0.9O2, its monoclinic phase was identified as a third crystal phase in the as‐fired sample with an amount of ~2.5 wt%, at the surface of polished (5.3 wt%) and roughened (8 wt%) specimens. In sum, the microstructure of the CMC material is homogeneous and can be modified by mechanical surface treatment leading to a partial transformation of the tetragonal phase of the Ce0.1Zr0.9O2 component into the monoclinic one. This partial transformation is also visible in AFM, with occurrence of transformation bands. The mechanism yield in surface compressive stress can be determined according to the Williamson and Hall method. The authors conclude that the absence of microcrack formation during polishing or roughening confirms the high flaw tolerance of such a CMC material.